Damage/collapse types of minarets for the February 6, 2023 Pazarcık and Elbistan earthquakes: Comparative evaluation of field studies and numerical analyses - Yetkin, Musa; Dedeoglu, Ibrahim O.; Erkek, Hakan; Calayir, Yusuf (Elsevier Sci Ltd, 2026)
In this paper, field studies were conducted to investigate the damage/collapse types of minarets during the February 6, 2023 earthquakes. For this purpose, field studies were conducted on the minarets of mosques in Gaziantep, Hatay, Kahramanmaras,, Osmaniye and S,anl & imath;urfa, which were among the provinces most affected by the February 6, 2023 earthquakes. For the minarets that were found to be damaged/collapsed, the deficiencies, errors and defects that were thought to have caused the collapse were identified and solutions were proposed for the repair and strengthening of such damages. After the field studies, surveys were conducted for three minarets that were damaged but not collapsed and finite element modeling was performed for these minarets. Then, considering the locations of these minarets, nonlinear earthquake analyses were performed under the closest station records of the February 6, 2023 earthquakes. The results obtained are compared and discussed with the current damage condition of the minarets.
Keywords: February 6; 2023 earthquakes; Field studies; Minarets; Nonlinear analysis